EDUKASI BAHAYA KONSUMSI JUNK FOOD DAN UPAYA PROMOSI POLA MAKAN SEHAT PADA REMAJA DI SMAN 1 SUKOHARJO - Renowening, Yuniars; Ridha, Alfan; Noviati, Titik Dwi; Mahmudah, Himmatunnisak; Maharani, Puan (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Adolescents are a vulnerable age group prone to dietary changes influenced by modern lifestyles. One emerging issue is the high consumption of junk food, which is associated with increased risks of obesity, type 2 diabetes mellitus, hypertension, and metabolic disorders. This community service activity aimed to provide education on the dangers of junk food and encourage adolescents to adopt healthier eating patterns. The method employed was interactive education through material delivery, group discussions, and short quizzes as an evaluation tool. The results demonstrated an improvement in adolescents’ knowledge of the negative impacts of junk food and raised awareness to begin reducing its consumption. This activity is expected to serve as an initial step toward building sustainable healthy eating behaviors among adolescents, thereby contributing to efforts to improve public health.